Informational motives of some etnonyms - Seiitova Ш.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The vital meaning of the national spirit is preserved in its language. Therefore, any semantic unit is an important part of the life of the tribe. The Kazakh people have their own art of expression. People who possessed the gift of eloquence were especially respected by the people. For this reason, it is possible to single out the national speech features of the oratory of the Kazakh people. The delicate messenger of the soul is preserved in his ego. Anyone who likes to be one of the most important parts of life. The art of the Kazakh people has its own art. There are ten great art lovers and artists. Everyday life is the main thing for the soul and language - this is an economic community. Ego vliyanje and vliyaniytsya are exclusively. The economical Society creates language specifications in the specific region and preserves these languages’ specifications in the form of plugs and plugs.